The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1038/sj.ijo.0802778
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and impaired fibrinolysis: role of adipose production of plasminogen activator inhibitor-1

Abstract: Obesity is the central promoter of the metabolic syndrome which also includes disturbed fibrinolysis in addition to hypertension, dyslipidaemia and impaired glucose tolerance/type 2 diabetes mellitus. Plasminogen activator inhibitor-1 (PAI-1) is the most important endogenous inhibitor of tissue plasminogen activator and uro-plasminogen activator, and is a main determinant of fibrinolytic activity. There is now compelling evidence that obesity and, in particular, an abdominal type of body fat distribution are a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
203
2
13

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 271 publications
(227 citation statements)
references
References 74 publications
9
203
2
13
Order By: Relevance
“…Subsequently when we conducted a multiple regression analysis on Japanese subjects whose BMIs were greater than 25 kg/m 2 , we observed a marginal association of insulin with PAI-1 levels (data not shown). Studies in human adipocyte indicate that PAI-1 synthesis is upregulated by insulin 28 but the upregulation of PAI-1 synthesis by insulin may be evident only in obese subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently when we conducted a multiple regression analysis on Japanese subjects whose BMIs were greater than 25 kg/m 2 , we observed a marginal association of insulin with PAI-1 levels (data not shown). Studies in human adipocyte indicate that PAI-1 synthesis is upregulated by insulin 28 but the upregulation of PAI-1 synthesis by insulin may be evident only in obese subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Second, there may be the differences in the fat cell size between these two ethnic groups. Americans may have smaller fat cells 28 than the Japanese as smaller fat cells produce less PAI-1 compared to larger fat cells [30][31][32] . Third, it may be explained by the differences in genetic factors between these ethnic groups.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Increased PAI-1 levels are responsible for the impaired fibrinolysis that accompanies obesity and presumably contribute to increased cardiovascular risk in overweight and obese individuals. 3 Moreover, the apparent association between PAI-1 plasma levels, and insulin resistance 4 and incident type 2 diabetes mellitus 5 characterizes PAI-1 as a biological marker of the metabolic risk that accompanies (visceral) obesity.…”
Section: Introductionmentioning
confidence: 99%
“…Despite a large body of epidemiological and experimental evidence in support of a direct link between (visceral) adipose tissue and plasma PAI-1 levels, 1,2,6 clinical evidence is less obvious and the molecular basis for the association between (visceral) adipose tissue and plasma PAI-1 levels in man is still unclear. 7 The most obvious explanation for the association between plasma PAI-1 levels and visceral adipose tissue is a direct link in which the elevated plasma PAI-1 levels in (visceral) obesity result from PAI-1 release from (visceral) fat mass.…”
Section: Introductionmentioning
confidence: 99%
“…Adipose tissue is now recognized as an endocrine organ that secretes many cytokines and growth factors. 4,5 For example, several reports have demonstrated that adipocytes secrete tumor necrosis factor alpha, 6 resistin, 7 plasminogen activator inhibitor-1 (PAI-1), 8 leptin 9 and angiotensinogen. 10,11 Vascular endothelial growth factor (VEGF) is an angiogenetic growth factor, which is secreted by rat adipose tissue ex vivo.…”
Section: Introductionmentioning
confidence: 99%